Aberrant accrual of BIN1 near Alzheimer's disease amyloid deposits in transgenic models. (27th December 2018) - De Rossi, Pierre; Andrew, Robert J.; Musial, Timothy F.; Buggia‐Prevot, Virginie; Xu, Guilian; Ponnusamy, Moorthi; Ly, Han; Krause, Sofia V.; Rice, Richard C.; de l'Estoile, Valentine; Valin, Tess; Salem, Someya; et al.
Abstract: Bridging integrator 1 ( BIN1 ) is the most significant late‐onset Alzheimer's disease (AD) susceptibility locus identified via genome‐wide association studies. BIN1 is an adaptor protein that regulates membrane dynamics in the context of endocytosis and membrane remodeling. An increase in BIN1 expression and changes in the relative levels of alternatively spliced BIN1 isoforms have been reported in the brains of patients with AD. BIN1 can bind to Tau, and an increase in BIN1 expression correlates with Tau pathology. In contrast, the loss of BIN1 expression in cultured cells elevates Aβ production and Tau propagation by insfluencing endocytosis and recycling. Here, we show that BIN1 accumulates adjacent to amyloid deposits in vivo . We found an increase in insoluble BIN1 and a striking accrual of BIN1 within and near amyloid deposits in the brains of multiple transgenic models of AD. The peri‐deposit aberrant BIN1 localization was conspicuously different from the accumulation of APP and BACE1 within dystrophic neurites. Although BIN1 is highly expressed in mature oligodendrocytes, BIN1 association with amyloid deposits occurred in the absence of the accretion of other oligodendrocyte or myelin proteins. Finally, super‐resolution microscopy and immunogold electron microscopy analyses highlight the presence of BIN1 in proximity to amyloid fibrils at the edges of amyloid deposits. These results reveal the aberrant accumulation of BIN1 is a feature associated with AD amyloid pathology. Our findings suggest a potential role for BIN1 in extracellular Aβ deposition in vivo that is distinct from its well‐characterized function as an adaptor protein in endocytosis and membrane remodeling.